Formação continuada de professores que ensinam Matemática nas séries iniciais : uma experiência em grupo - Bertucci, Monike Cristina Silva (Universidade Federal de São Carlos, 2009)
Taking the profession difficulties of teachers in general and challenges of teaching practices, there is always a need for continuous training. Considering that need, this research has studied the practices which were developed by those professionals of the group for continuing education of mathematics teachers in starting years of elementary school . In addition, the goal of this research is also understand the professional skills that were learnt from those practices and also the influence of public policies on that process. The actions of this research were guided by the following questions: How does a teacher group from a public school in São Paulo state develop themselves through a process of thinking, study and analysis of their practices of teaching and learning mathematic during starting years of elementary school? What are the influences of public policies, problems and internal difficulties of schools in that process? The research methodology adopted for answering those questions was a study case, developed within a qualitative approach It using the following tools for taking relevant data for the research: participant observation, asking, narrative and semi-structured interview during the working time. Taking a process of multiple readings, organization and understanding the meaning of data it was possible to built two emerging analysis categories: 1. Practices of teacher education and 2. Influences public policy. The theoretical study covering two main areas: the continuing teachers training and professional development. Authors such as Freire (1979, 1986, 1994 and 1996), Nóvoa (1992), Charlot (2000; 2005), Nacarato (2000; 2003; 2005), Fiorentini and Nacarato (2005), Bozzini and Oliveira (2006) and Imbernón (2006, 2009) we tried to understand the continuing education focused on school, from the mobilization their professionals, based on group reflection, in the reorganization of the HTPC and in research perspective with teachers. By the way, Mizukami (1996), Ponte (1998), Passos et al. (2006), Gama (2007) and Hargreaves et al. (2002) helped us with discussions of professional development. The results indicate that when there is the existence of a favorable environment, like the one examined by this research facilitates the process of continuing education, enhances professional development and contribute to teachers training needs. The main characteristics of this favorable environment are the mobilization of school professionals in meeting the challenges and domestic needs, the support of school management in the development of training practices and the presence of the external agent during the meetings of the study group at school, to share knowledge, experiences and to promote collective reflection on teaching practices of mathematics in the early grades of elementary school.
Keywords: Professores - formação; Séries iniciais; Matemática - ensino; Profissões - desenvolvimento; Continuing teachers education; Mathematic teaching; Starting years of elementary school; Professional development; CIENCIAS HUMANAS::EDUCACAO